Ksiądz profesor dr Aleksander Usowicz CM. Wspomnienia - Kubiś, Adam (Analecta Cracoviensia, 2012)
The paper presents the personality and the scientific record of Rev. prof. Aleksander Usowicz CM. He was an acknowledged representative of the neo-Scholasticism, the main philosophical movement in the mid 50 of 20th c. at the Theological Faculty of the Jagiellonian University in Krakow.In fact, scientific interest of Usowicz went beyond the field of philosophy. He was also interested in theology. Among many lecturers he delivered, the most important was one about the introduction to theology. Its aim was to provide students with the basics of the history of theological thought.It must be remembered that Usowicz was a reviewer of the habilitation work of Fr. Karol Wojtyła. He was also a tutor and scientific supervisor of many later professors of philosophy and theology.